(3GdeQL GdfVQ hGdCQL GdYWQs - (3eMeO Hf CHj HcQ Hf Ydj Hf MSf, UdGM GdOjf GdMSfj GdSjhWj,J (B856 (3g` s ((3Ydj Hf CMeO Hf YeQ Hf Nda Hf eMehO GdSNGhj GdMfaj s)
(3ChdgG (B:s
(3CeG HYOaEf aj GdCOH YRjR GSJMSfg GdSda, hJMdi Hg ef HYOge GdNda s
(3BNQgG (B:s
(3hbGd eWQa Gfj dCSJdbj HGddjd Ydi aQGTj aCJOHQ GdbQCf aCQLh Cf Cchf CfG hCfJe jG ENhGffG efge hgPG BNQ eG JjSQ LeYg aj gPG GdcJGH s
(3GfXQ GdLRA GdChd Qbe (B759 (3COHs
(3QJHg Ydi NeSI CHhGHs
(3cd HGH jMJhj Ydi NeSI aUhds
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs